Basics of security and cryptography - Pathan, Al-Sakib Khan (CRC Press, Taylor & Francis Group, USA, 2014)
To begin with, the purpose of this book is not to delve into the history of cryptography or to analyze the debate on the first occurrence of the technique in communications technologies. Instead, we aim to clarify various basic terminologies to give lucid understanding of the subject matter. Throughout the book, we will see various approaches to utilizing cryptographic techniques along with practical codes; however, the intent of this first chapter is to set the basics for the rest of the content.